Potential uses of indigenous cucumis africanus and cucumis myriocarpus as root-knot nematode-resistant rootstocks in watermelon (citrullus lanatus ) husbandry - Pofu, Kgabo Martha (University of Limpopo ( Turfloop campus), 2012)
Global withdrawal of synthetic fumigant nematicides like methyl bromide due to their eco-unfriendliness resulted in serious consequences in production of crops which do not have genotypes that are resistant to plant-parasitic nematodes. Watermelon (Citrullus lanatus) is one such crop, where infection by highly aggressive root-knot nematodes (Meloidogyne species) invariably results into as high as 50% yield loss, with occasional total crop failures. Initial screening for nematode resistance in Cucumis species indigenous to South Africa suggested the possibility of the existence of nematode resistance, with the probability of these species being compatible with Citrullus species in inter-generic grafting technology. Uses of indigenous genera in Cucurbitaceae family as nematode-resistant seedling rootstocks in watermelon production could promote the South African watermelon industry as outlined in ISO 9001 certification guidelines to have competitive advantage in lucrative watermelon export markets. The objectives of this study were to determine the: (1) host-status and host-sensitivity of C. africanus and C. myriocarpus seedlings using a series of inoculation levels of M. incognita race 2 under various conditions, (2) host-status and host-sensitivity of C. africanus and C. myriocarpus seedlings using a series of inoculation levels of M. incognita race 4 and M. javanica, including the resistance form in these plant species, at least, under selected environmental conditions, (3) host-status and host-sensitivity of C. africanus and C. myriocarpus seedlings using a series of inoculation levels of M. incognita race 2 with multi-nematode xxviii infestations in order to establish whether the observed nematode resistance was sustainable when the plant was attacked by various pests at the root system level, (4) compatibility of inter-generic grafting of Citrullus and Cucumis seedlings in order to establish the potential uses of Cucumis species in olericulture, and (5) influence of the greenhouse whitefly (Trialeurode vaporariorum) infection on resistance of C. africanus to Meloidogyne species in order to establish whether the observed nematode resistance was sustainable when the plant was attacked by pests on complimentary organs. Reliability of measured variables was ensured by using statistical levels of significance (P ≤ 0.05) and coefficient of determination (R2), with validity being ensured by conducting experiments at the same location over two seasons or conducting one experiment during one season at two different locations, viz. the University of Limpopo and the Agricultural Research Council – Institute for Industrial Crops, and/or by setting up factorial treatments. Results consistently demonstrated that C. africanus and C. myriocarpus were non-hosts to M. incognita races 2 and 4 and M. javanica, without the test nematodes inflicting any damage to plants, which in plant-parasitic nematodes is described as nematode resistance. Quadratic relationships between RF values and log10(Pi + 1) transformations, in addition to confirming the density-dependent growth patterns of plant-parasitic nematodes, also suggested that chemical compounds responsible for suppression of nematodes in the two Cucumis species were different. The two Cucumis species were resistant to M. incognita races 2 and 4 and M. javanica, regardless of the environment under which the experiments were conducted. In field studies, the xxix two Cucumis species supported the ring nematodes (Criconema mutabile) and the spiral nematodes (Helicotylenchus dihystera), without these exo-parasitic nematodes inflicting any damage to plants, which in plant-parasitic nematodes is described as tolerance. Interactions among Meloidogyne species, C. mutabile and H. dihystera were either stimulatory or inhibitory, depending on whether Meloidogyne species were in the soil or inside the roots. Mechanisms of nematode resistance in the two Cucumis species were different, with C. africanus and C. myriocarpus depicting pre-infectional and post-infectional forms of resistance, respectively, without any sign of hypersensitivity in roots. When, seeds of Citrullus species were primed in water to hasten germination. Using the developed technology, survival of grafts improved from 36% to 100%, translating to relative improvement of 178%, with nematode-resistant rootstocks retaining their nematode resistant capabilities, while watermelon scions flowered earlier, with relatively higher fruit yield, without any deleterious effect on accumulation abilities of essential nutrient elements in leaves. Resistance of C. africanus to M. javanica was invariably broken by the greenhouse whitefly infection at high population levels, possibly through loss of non-structural carbohydrates, which are essential in synthetic pathways of secondary metabolites. Cucumis africanus and C. myriocarpus contain cucurbitacin B (C32H48O8) and cucurbitacin A [cucumin (C27H40O9), leptodermin (C27H38O8)], respectively, which have high demand for carbon and energy. Consequently, the efficacy of indigenous Cucumis species as nematode-resistant rootstocks in suppression of Meloidogyne species would be dependent upon the management of the xxx greenhouse whitefly population densities. In conclusion, C. africanus and C. myriocarpus have the potential for use as nematode-resistant rootstocks in the production of watermelon cultivars ‘Congo’ and ‘Charleston Gray’ in South Africa, where nematode population densities of M. incognita races 2 and 4 and M. javanica are widely distributed and are highly injurious to watermelons. Although nematode resistance in the two Cucumis species had attributes of sustainability, populations of the greenhouse whitefly broke the resistance. Proposed future research areas included influence of cucurbitacins in fruit quality of watermelons and protocols for mass culturing the nematode-resistant Cucumis rootstocks using tissue culture technology.
Thesis (Ph.D. (Plant Protection)) --University of Limpopo, 2012
Keywords: Indigenous cucumis africanus; Cucumis myriocarpus; Watermelon (citrullus lanatus); 635.615; Watermelons